2020
DOI: 10.1007/s10006-020-00838-7
|View full text |Cite
|
Sign up to set email alerts
|

A decade of reconstructive surgery: outcome and perspectives of free tissue transfer in the head and neck. Experience of a single center institution

Abstract: Purpose Free flaps have become the standard option in reconstructive surgery of the head and neck. Even though many authors have outlined the reliability of free transplants, there is an ongoing discussion about treatment options for patients bearing particular risks as previous irradiation treatment. In this analysis, we aim to address these patients with particular risk profiles by comparing different flap entity outcome parameters. Methods We retrospectively analyzed a cohort of 494 patients who underwent f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
(20 reference statements)
0
17
0
1
Order By: Relevance
“…Free flap reconstruction currently represents the first choice in managing complex maxillofacial defects because their functional and esthetic results and donor site morbidity rates are better than those of pedicled flaps [ 11 ]. Free flaps, which can also be successfully used in elderly patients, also have similar transplant survival rates [ 3 , 12 ]. However, several publications have shown that perioperative local and systemic complications directly correlate with increased age and particularly with the presence of relevant comorbidities [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Free flap reconstruction currently represents the first choice in managing complex maxillofacial defects because their functional and esthetic results and donor site morbidity rates are better than those of pedicled flaps [ 11 ]. Free flaps, which can also be successfully used in elderly patients, also have similar transplant survival rates [ 3 , 12 ]. However, several publications have shown that perioperative local and systemic complications directly correlate with increased age and particularly with the presence of relevant comorbidities [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…As described recently, free flap reconstruction represents the state of the art procedure at our department, and patients undergoing this procedure are of advanced age [ 3 ]. However, we have observed that the age at which patients require advanced maxillofacial flap reconstruction is increasing; thus, patients often present with a higher number of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 A recent study by Spoerl et al reported pectoralis major myocutaneous flap closure as having a slightly lower success rate (88%; N ¼ 40) than radial forearm free flap (93%; N ¼ 230), the same as free fibula flap (88%; N ¼ 121) but higher than anterolateral thigh flap closure (82%; N ¼ 51). 12 Therefore, even though free flaps may be preferable in typical situations, in times of social crises and limited resources, the pectoralis major flap offers a viable alternative.…”
Section: Outcomes Of Regional Versus Free Flapsmentioning
confidence: 99%
“…Moreover, in defects with extensive hard and soft tissue loss in the OMF complex, loco-regional flaps and microvascular free tissue transfer is still considered as the superior reconstructive option [ 3 , 4 ]. However, despite high success rates of both vascularized and non-vascularized grafts, such reconstructive options still have critical disadvantages including, mainly, donor-site morbidity, availability in limited quantities, prolonged anesthesia time, unpredictability of bone graft resorption, total flap loss, and the need to manually sculpt the graft into the shape of the defect site [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%